Potential oxidative stress related targets of mitochondria-focused therapy of PTSD - Kmita, Hanna; Pinna, Graziano; Lushchak, Volodymyr I. (Frontiers in Physiology, 2023)
Post-traumatic stress disorder (PTSD) remains a highly prevalent, under-diagnosed, and under-treated psychiatric disorder that often deteriorates over time, and is highly comorbid with major depressive disorder, suicidality, and substance use disorder. Several biomarkers have been proposed but have yet to be implemented into clinical practice. Treatments, including selective serotonin reuptake inhibitors, are efficacious in only a small number of patients, which underscores the need to develop novel, efficient treatments. Mitochondrial dysfunction resulting from chronic oxidative stress has been linked with both altered neurotransmitter signaling and the inflammatory response. Hereinafter, we discuss mechanisms by which mitochondrial dysfunction may contribute to the development of PTSD symptoms, and how these may even increase PTSD susceptibility. We also highlight possible therapeutic targets to reduce oxidative stress to prevent or treat PTSD symptoms.